2020
DOI: 10.1172/jci.insight.138137
|View full text |Cite
|
Sign up to set email alerts
|

Human C. difficile toxin–specific memory B cell repertoires encode poorly neutralizing antibodies

Abstract: Clostridioides difficile is a leading cause of nosocomial infection responsible for significant morbidity and mortality with limited options for therapy. Secreted C . difficile toxin B (TcdB) is a major contributor to disease pathology, and select TcdB-specific Abs may protect against disease recurrence. However, the high frequency of recurrence suggests that the memory B cell response, essential for new Ab production following C .… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 90 publications
0
10
0
Order By: Relevance
“…In fact, several reports show that defective B responses might be an important factor in C. difficile disease recurrence. Low concentrations of neutralizing anti‐TcdB and anti‐TcdA Abs, 88 memory B cell‐encoded Abs with low to moderate affinity for TcdB, and limited ability to neutralize TcdB, 89 as well as host genetic variations located in the extended major histocompatibility complex, 90 have been proposed to explain recurrent CDI.…”
Section: The Adaptive Immune Response Against Clostridioides Difficilementioning
confidence: 99%
“…In fact, several reports show that defective B responses might be an important factor in C. difficile disease recurrence. Low concentrations of neutralizing anti‐TcdB and anti‐TcdA Abs, 88 memory B cell‐encoded Abs with low to moderate affinity for TcdB, and limited ability to neutralize TcdB, 89 as well as host genetic variations located in the extended major histocompatibility complex, 90 have been proposed to explain recurrent CDI.…”
Section: The Adaptive Immune Response Against Clostridioides Difficilementioning
confidence: 99%
“…It is possible that a lack of T cell help may have limited memory B cell expansion and differentiation into antibody-secreting plasma cells in this non-responder, or that their toxin A-and B-expressing memory B cells, which increased 2 weeks post-final FMT, only encoded low-affinity antibodies incapable of toxin neutralization. In support of this latter hypothesis, Shah and colleagues recently demonstrated that human C. difficile toxin-specific memory B cell repertoires encode poorly neutralizing antibodies, with limited class switching and IgM dominance [71]. These findings indicate that memory B cells may be an important factor in C. difficile disease recurrence.…”
Section: Discussionmentioning
confidence: 89%
“…Maintenance of toxin B memory cell response was poor, as mice were unable to elicit protection upon rechallenging with C. difficile spores [278]. Sequencing revealed somatic hypermutations but limited isotype class switching in anti-toxin B antibodies in B memory cells and monoclonal antibodies generated displayed low to moderate affinity without a strong neutralizing ability [279]. Despite the brief longevity of circulating antibodies from B memory cells, anti-toxin antibodies have been long described to be effective at protecting the host against CDI.…”
Section: Adaptive Immune Responsesmentioning
confidence: 99%